Narrow bandgap semiconductors for infrared photodetection - Bai, Lu (2013)
Infrared (IR) detectors are very important in both military and civilian applications and have been widely investigated over the past century. Commercial applications of IR FPAs could cover medical, fire control, surveillance and driver’s vision enhancement. The military applications could include night vision, rifle sight, surveillance, missile guidance, tracking, and interceptors. IR FPAs with high sensitivity, high uniformity, large format, and flexible wavelength are needed from the short wavelength infrared (SWIR) to very long wavelength infrared (VLWIR) spectral range. High sensitivity is desirable for advanced IR sensor systems and the stability, reproducibility, yield, cost, maintenance, and manufacturability are also very important issues. This project aims at characterizing the narrow bandgap materials and optimizes their properties suitable for infrared photodetection.